Bisphenol AF exerts estrogenic activity in MCF-7 cells through activation of Erk and PI3K/Akt signals via GPER signaling pathway. (April 2019) - Lei, Bingli; Sun, Su; Zhang, Xiaolan; Feng, Chenglian; Xu, Jie; Wen, Yu; Huang, Yangen; Wu, Minghong; Yu, Yingxin
Abstract: The negative health effects of bisphenol A (BPA) due to its estrogenic activity result in the increasing usage of alternative bisphenols (BPs) including bisphenol AF (BPAF). To comprehensive understand health effects of BPAF, the MCF-7 cells were used to investigate the effects of BPAF on cell proliferation, intracellular reactive oxygen species (ROS) formation, and calcium ion (Ca 2+ ) level. The molecular mechanisms of cell biological responses caused by BPAF were investigated by analyzing target protein expression. The results showed that low-concentration BPAF induces significant effects on MCF-7 cells, including promoting cell proliferation and elevating intracellular ROS and Ca 2+ levels. BPAF in low concentration significantly enhances the protein expression of estrogen receptor α (ERα), G protein-coupled receptor (GPER), c -Myc, and Cyclin D1, as well as increases phosphorylation levels of protein kinase B (Akt) and extracellular signal-regulated kinase (Erk) in MCF-7 cells. After the addition of ERα, GPER, and phosphatidylinositide 3-kinase (PI3K) inhibitors, phosphorylations of Erk and Akt were both inhibited. In addition, specific signal inhibitors significantly attenuated the effects of BPAF. Silencing of GPER also markedly decreased BPAF induced cell proliferation. The present results suggested that BPAF can activate PI3K/Akt and Erk signals via GPER, which, in turn, stimulate cellular biological effects induced by BPAF. ERα also plays a critical role in BPAF induced cellular biological effects. Graphical abstract: Image 1 Highlights: BPAF promotes cell proliferation, and elevates ROS and Ca 2+ levels in MCF-7 cells. BPAF activates PI3K/Akt and Erk signaling pathways via GPER. Activation of GPER mediated signals stimulates BPAF induced cell biological effects. ERα plays a key role in cell biological effects induced by BPAF. BPAF can exert estrogenicity by interactions between ERα and GPER mediated signals.